Birds of the Kangchenjunga Landscape, the Eastern Himalaya: status, threats and implications for conservation - Pratikshya Kandel; Ishana Thapa; Nakul Chettri; Rebecca Pradhan; Eklabya Sharma (Avian Research, 2018)
Abstract Birds are reliable and widely used indicators for conservation planning and monitoring. We reviewed birds of the Kangchenjunga Landscape, a transboundary complex shared by Bhutan, India and Nepal in the Eastern Himalaya. Using 119 literature, we analyzed the bird survey efforts in the landscape, their taxonomic representation, global threat status, distribution patterns, and habitat preferences. We also discussed the potential threats and conservation challenges and documented current conservation efforts and government policies. Most of the bird surveys are carried out in India followed by Nepal and Bhutan. A total of 618 bird species belonging to 19 orders and 77 families are recorded. Passeriformes is the dominant order that constitutes 62% of the total records listed from the landscape. Among the families, Muscicapidae is the most common and diversely represented family. There are 41 species of birds that are categorized as threatened under IUCN Red List. Of the total birds occurring in the landscape, the highest number of bird species (95%) was documented from India, followed by Nepal (55%) and Bhutan (34%). Of them, 24% of the species were found to occur in the tropical zone. Forested habitat is widely used by 63% of the total species followed by wetlands (16%). Despite promising policies and legal provisions, the landscape faces numerous challenges including habitat loss and fragmentation, hunting and trapping, unsustainable extraction of natural resources, invasive alien species, unregulated tourism and global climate change. We suggest protection and management of birds through strengthening Important Bird and Biodiversity Areas, reduction in forest encroachment and habitat destruction, conservation awareness programmes and comprehensive bird surveys with long term monitoring to assess the impact of environmental change as some of the approaches to conserve the rich avifaunal diversity of the landscape.